Sistem Keamanan Ruangan Menggunakan ESP32CAM dan Sensor Gerak Berbasis IoT - Humam, Faris; Triawan, Muhammad Agus (Fakultas Teknik Universitas Hamzanwadi, 2024)
In the current digital era, the demand for effective and efficient security systems is increasing. This research develops a room security system using ESP32CAM and motion sensors based on the Internet of Things (IoT). The system is designed to detect movement within a room and send real-time notifications to users via a mobile application. The ESP32CAM functions as a surveillance camera that captures images when the motion sensor detects activity. Data from the motion sensor and images from the ESP32CAM are sent to a cloud server for processing and storage. System testing shows that this solution can provide a quick response to movement, send notifications within seconds, and securely store data in the cloud. Thus, this system can significantly enhance room security and provide peace of mind to its users